إيجارات أوقاف اليهود السكنية بالفسطاط في العصر الأيوبي مع دراسة عقد إيجار سكن في أوقاف اليهود الربانيين ونشره مؤرخ في 2 شعبان سنة 626 هـ. / 25 يونيو 1229 م. - علي، عمر جمال محمد Ali, Omar Jamal Mohammed (اتحاد المؤرخين العرب بالقاهرة, 2022)
تتناول هذه الدراسة إيجارات أوقاف اليهود السكنية بالفسطاط في العصر الأيوبي، مع دراسة عقد إيجار سكن في أوقاف اليهود الريانين ونشره، المؤرخ في الثاني من شعبان سنة ٦٢٦ ه/ ٢٥ يونيو ١٢٢٩م، وجاءت افتتاحية الدراسة عن التجمعات السكنية لليهود وأعدادهم، وطوائفهم الدينية في مدينة الفسطاط، ثم تطرقت الدراسة إلى طرق تسجيل الإيجارات العقارية السكنية واستخراج أجرتها؛ وفقا لما ورد في كتب علم الشروط؛ وذلك لفهم نظام الإيجارات في العصر الأيوبي، ثم دراسة إيجارات أوقاف اليهود السكنية، وكيفية تحصيل إيراداتها، وسبل إنفاقها في مصارفها المختلفة في ضوء وثائق الجنيزة. وتأسيسا على ما سبق اقتضت طبيعة المعلومات الواردة بالقوائم الحسابية الجبائية الخاصة بإيجارات العقارات السكنية أن تشتمل على طرح للتعريف بنظام الوقف اليهودي الذي عرف باسم: القودش أو الهقديش، والذي يماثل نظام الوقف الإسلامي، وكان يسمى في وثائق الجنيزة-في بعض الأحيان -مصطلح الوقف أو الحبس، وكان يمنح بشكل رسمي للمحكمة القضائية اليهودية، التي استأثرت بإدارته، وأسندت إلى البرناس جباية المبالغ المستحقة عن إيجار العقارات، وقد وضعت بعض الضوابط والشروط للمستأجرين، وكان يصرف من إيرادات الإيجارات جزء كبير على الفقراء والمحتاجين، وصيانة المعابد، والعقارات الموقوفة وترميمها، ودفع الضرائب الحكومية، كذلك تفاوتت في قيمة الإيجار من مكان إلى آخر، وتأثرت بالكوارث الطبيعية كالمجاعات والأوبئة، واختتمت الدراسة بفهرسة عقد الإيجار من حيث الشكل والمضمون، ودراسة محتوياته، ونشر نصه وتحقيقه. This study deals with the rents of the Jewish residential endowments in al- Fusṭāṭ in the Ayyūbid period. The study is a close investigation and publication of a housing Deed of Lease in the Rabbanite Jews Awqāf; the lease is dated on 2 Shaban 626 AH / 25 June 1229 AD. The study commences with a survey on the Jewish residential communities and their numbers and their religion sects in al-Fustāt. In order to understand the rental system in the Ayyūbid period, the study reviews the methods of registering and extracting the rents of the residential real estate according to what was stated in the Shurūṭ books. Thereafter, the study appraises the rents of the residential Jewish Awqaf (endowments), the ways of collecting their revenues, and the ways of their expenditures in the light of the Geniza documents. Based on the foregoing, the nature of the information in the rental accounts of the residential real estate required a definition of the Jewish endowment system known as: Al-Qōdesh or Al Heqdēsh, which is similar to the Islamic wqaf system. In the Geniza documents, it was - sometimes - called by the term wqaf or ḥabs. The Jewish Judicial Court was officially granted the right to administer the jewish waqf and sometimes solely took responsibility for managing the waqf. The Jewish Judicial Court entrusted the Parnās for the jibāyat (the collection) of the amounts due for renting real estate and placed some controls and conditions on the tenants. A large part of the rental revenues was spent on serving the poor and the needy, maintaining the Synagogues, maintaining and restoring the endowed properties, and paying the Government taxes. The value of rents varied from one place to another and rents were affected by natural disasters such as famine and epidemics. The study concludes with indexing the deed of lease in terms of form and content, examining its contents, publishing and editing its text.
Keywords: الوقف الإسلامي -- عقود الإيجار -- الإيجار العقارية -- العصر الأيوبي -- مدينة الفسطاط